2017
DOI: 10.1128/jvi.02404-16
|View full text |Cite
|
Sign up to set email alerts
|

Viral RNA at Two Stages of Reovirus Infection Is Required for the Induction of Necroptosis

Abstract: Necroptosis, a regulated form of necrotic cell death, requires the activation of the RIP3 kinase. Here, we identify that infection of host cells with reovirus can result in necroptosis. We find that necroptosis requires sensing of the genomic RNA within incoming virus particles via cytoplasmic RNA sensors to produce type I interferon (IFN). While these events that occur prior to the synthesis of viral RNA are required for the induction of necroptosis, they are not sufficient. The induction of necroptosis also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
98
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(102 citation statements)
references
References 83 publications
(135 reference statements)
4
98
0
Order By: Relevance
“…To determine the stage of the reovirus replication cycle that is required for the loss of the IKK complex and the inhibition of NF-κB, we treated cells with ribavirin, which diminishes viral gene expression (13, 22). We found that ribavirin treatment prevented T3A mediated loss of IKKβ (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the stage of the reovirus replication cycle that is required for the loss of the IKK complex and the inhibition of NF-κB, we treated cells with ribavirin, which diminishes viral gene expression (13, 22). We found that ribavirin treatment prevented T3A mediated loss of IKKβ (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This outcome, at least in part, is due an inability of p50−/− mice to produce IFNβ. Despite the fact that the viral genomic RNA remains within the two concentric protein shells that comprise the reovirus capsid, the current model posits that the innate immune response is initiated when genomic RNA from incoming virions is sensed by the RLRs - RIG-I and MDA5 (9, 13). The sensing of the RNA leads to the activation of IRF3 and NF-κB, which lead to the production of IFN and other inflammatory cytokines (14).…”
Section: Introductionmentioning
confidence: 99%
“…Additional sensors that initiate necroptosis following virus infection likely exist, as infection of L929 cells with the T3D strain of respiratory enteric orphan virus (reovirus) induces caspase-independent cell death [52] (Figure 1). Cell death following T3D infection is dependent on de novo synthesis of viral dsRNA and requires RIPK1, but is independent of the known initiators of necroptosis, TNFR, DAI or TLR3 [81]. In addition, this response requires production of IFN and signaling through the type I IFN receptor, suggesting an IFN stimulated gene(s) might sense or regulate reovirus-mediated cell death [81].…”
Section: Similar To MCMV Influenza a Virus (Iav) Infection Induces Cmentioning
confidence: 99%
“…Cell death following T3D infection is dependent on de novo synthesis of viral dsRNA and requires RIPK1, but is independent of the known initiators of necroptosis, TNFR, DAI or TLR3 [81]. In addition, this response requires production of IFN and signaling through the type I IFN receptor, suggesting an IFN stimulated gene(s) might sense or regulate reovirus-mediated cell death [81]. Further identification and characterization of this response remains an important area of future study.…”
Section: Similar To MCMV Influenza a Virus (Iav) Infection Induces Cmentioning
confidence: 99%
“…Reovirus induces programmed cell death in vitro and in vivo (2330). Although both Type 1 and Type 3 reovirus can induce apoptosis, Type 3 reoviruses induce apoptosis and necroptosis more efficiently in most cells (18, 23, 24). Serotype-dependent differences in apoptosis induction segregate with the S1 and M2 gene segments (3133).…”
Section: Introductionmentioning
confidence: 99%